Late-life depressive symptoms and lifetime history of major depression: cognitive deficits are largely due incipient dementia rather than depression - Heser, Kathrin; Weyerer, Siegfried (Journal of Alzheimer's disease, 2016)
Background: Late-life depression is frequently accompanied by cognitive impairments. Objective: Whether these impairments indicate a prodromal state of dementia, or are a symptomatic expression of depression per se is not well-studied. Methods: In a cohort of very old initially non-demented primary care patients (n=2,709, mean age=81.1y), cognitive performance was compared between groups of participants with or without elevated depressive symptoms and with or without subsequent dementia using ANCOVA (adjusted for age, sex, and education). Logistic regression analyses were computed to predict subsequent dementia over up to six years of follow-up. The same analytical approach was performed for lifetime major depression. Results: Participants with elevated depressive symptoms without subsequent dementia showed only small to medium cognitive deficits. In contrast, participants with depressive symptoms with subsequent dementia showed medium to very large cognitive deficits. In adjusted logistic regression models, learning and memory deficits predicted the risk for subsequent dementia in participants with depressive symptoms. Participants with a lifetime history of major depression without subsequent dementia showed no cognitive deficits. However, in adjusted logistic regression models, learning and orientation deficits predicted the risk for subsequent dementia also in participants with lifetime major depression. Conclusion: Marked cognitive impairments in old age depression should not be dismissed as “depressive pseudodementia”, but require clinical attention as a possible sign of incipient dementia. Non-depressed elderly with a lifetime history of major depression, who remained free of dementia during follow-up, had largely normal cognitive performance.